On-Farm Evaluation of Tractor Drawn Wheat Seed Drill (International Journal of Precision Farming, 2023)
This experiment was conducted to evaluate the performance of a tractor-drawn wheat seed drill machine which can sow wheat and fertilizer at predetermined depths and row spacing. The machine performances were evaluated in terms of Seed and fertilizer rate, depth of seed placement, row spacing, plant population, field capacity, and field efficiency. Randomized complete block design with three forward speeds, three hopper loading, and three replications were used as experimental design. There were no visible or internal seeds damaged by the machine and it shows that there was no reduction in germination percentage when compared with the seed supplier recommendation. The seed and fertilizer rate was calibrated and recorded as 125 kg/ha and 150 kg/ha respectively for 20 cm row spacing. The seed drill was evaluated at speeds of 3, 4, 5 km/hr and hopper loading levels of H50, H75, and H100. Both the operating speed and hopper loading capacity of the machine had a significant effect on seed and fertilizer rate at p < 0.05. The average field capacity, field efficiency, and fuel consumption at 4km/hr speed of operation were 0.43 ha/hr, 85.93%, and 3.8 l/hr respectively. 378 to 380 plant populations per 1.2 m2 area were counted during seedling count. Depending on the results of the performance evaluation, it is concluded that the developed seed drill machine can be efficiently and economically used by the majority of farmers.